The contexts and early Acheulean archaeology of the EF-HR paleo-landscape (Olduvai Gorge, Tanzania). Issue 120 (July 2018) - de la Torre, Ignacio; Albert, Rosa M.; Macphail, Richard; McHenry, Lindsay J.; Pante, Michael C.; Rodríguez-Cintas, Ágata; Stanistreet, Ian G.; Stollhofen, Harald
Abstract: Renewed fieldwork at the early Acheulean site of EF-HR (Olduvai Gorge, Tanzania) has included detailed stratigraphic studies of the sequence, extended excavations in the main site, and has placed eleven additional trenches within an area of nearly 1 km 2, to sample the same stratigraphic interval as in the main trench across the broader paleo-landscape. Our new stratigraphic work suggests that EF-HR is positioned higher in the Bed II sequence than previously proposed, which has implications for the age of the site and its stratigraphic correlation to other Olduvai Middle Bed II sites. Geological research shows that the main EF-HR site was situated at the deepest part of an incised valley formed through river erosion. Archaeological excavations at the main site and nearby trenches have unearthed a large new assemblage, with more than 3000 fossils and artefacts, including a hundred handaxes in stratigraphic position. In addition, our test-trenching approach has detected conspicuous differences in the density of artefacts across the landscape, with a large cluster of archaeological material in and around the main trench, and less intense human activity at the same level in the more distant satellite trenches. All of these aspects are discussed in this paper in the light of site formation processes, behavioral contexts, and their implications for our understanding of the early Acheulean at Olduvai Gorge.